2020
DOI: 10.3390/ijms21041440
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Expression Induces Apoptosis in Human Non-Small-Cell Lung Cancer

Abstract: The prognostic value of Toll-like receptor 3 (TLR3) is debated in cancer, differing between tumor types, methods, and cell types. We recently showed for the first time that TLR3 expression on early stage non-small-cell lung cancer (NSCLC) results associated with a good prognosis. Here, we provide experimental evidences explaining the molecular reason behind TLR3’s favorable prognostic role. We demonstrated that TLR3 activation in vitro induces apoptosis in lung cancer cell lines and, accordingly, that TLR3 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 35 publications
(51 reference statements)
0
31
0
Order By: Relevance
“…The abnormal expression of TLR3 has been reported on various of cancer tissues (10,11). TLR3 has also been recognized as a favorable prognosis biomarker of lung cancer by activating apoptosis or promoting autophagy (12,13). TLR3 agonist enhanced T cell infiltration in lung tissue, which is essential for tumor immunity within the tumor microenvironment (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of TLR3 has been reported on various of cancer tissues (10,11). TLR3 has also been recognized as a favorable prognosis biomarker of lung cancer by activating apoptosis or promoting autophagy (12,13). TLR3 agonist enhanced T cell infiltration in lung tissue, which is essential for tumor immunity within the tumor microenvironment (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in vivo anti-tumor effects of TLR3 ligand, Poly(I:C) are possibly mainly due to an induction of cell death upon direct stimulation of TLR3 by TLR3 ligand, Poly(I:C) [24] and also the recruitment of tumor-specific CD8+ T lymphocytes [71]. TLR3 ligand, Poly(I:C) stimulation has been reported to induce cell death on itself or combination with sensitizers in several cancers, but lack of evidence in CCA [18][19][20][21][22][23][24][25][26][27][28][29][30][31][33][34][35][36]. Our results did demonstrate for the first time that Poly(I:C) itself did not induce CCA cell death but only in the presence of Smac mimetic, an IAP antagonist [72], the combination treatment significantly triggered apoptosis with high synergism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLR3 ligands have been studied in clinical trials as adjuvants for cancer immunotherapy to enhance cancer vaccine efficacy [15][16][17]. In addition to orchestrating inflammatory and immune responses, triggering TLR3 signaling by TLR3 ligands has been reported to directly kill various cancer cells such as breast cancer [18,19], melanoma [20,21], renal cell carcinoma (RCC) [22], prostate cancer [23,24], nasopharyngeal carcinoma [25,26], multiple myeloma [27], head and neck squamous cell carcinoma (HNSCC) [28][29][30], hepatocellular carcinoma (HCC) [31], neuroblastoma [32], non-small cell lung cancer (NSCLC) [33][34][35], and mesothelioma [36]. TLR3 ligands-mediated cell death is involved the formation of a signaling complex composed of TRIF, RIPK1, Fasassociated protein with death domain (FADD) and caspase-8, the death signaling complex also called ripoptosome [34,37].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism is Toll-Like Receptor 3 (TLR3, Table 1 ) agonists, and it was found that the activation of TLR3 in vitro can induce apoptosis in lung cancer cell lines. In addition, some studies support the use of TLR3 agonists in patients with non-small cell lung cancer (NSCLC) to reactivate the local innate immune response ( Bianchi et al, 2020 ).…”
Section: Launched and Ongoing Drugsmentioning
confidence: 99%